Role of Services in the Economies of Small Towns of Silesia Region and Wielkopolskie Voivodehip - Konecka-Szydłowska, Barbara; Zuzańska-Żyśko, Elżbieta; Szmytkie, Robert (Bulletin of Geography. Socio-economic Series, 2010)
The main aim of the article is to determine the role of services in the economies of small towns of Silesia and Wielkopolska (Greater Poland) regions. It will be achieved through the following steps: (A) characteristic of the set of towns under study, (B) determination of the share of services in their economies, and (C) description of their level of service development. The analysis rests on two criteria employed at each stage of the research: (a) that of location, which embraces the voivodships: Dolnośląskie, Opolskie, Śląskie (Silesia region) and Wielkopolskie voivodship and (b) that of size, with three classes of small towns distinguished: up to 5 thousand, 5-10 thousand, and 10-20 thousand population.